Personalized Sustainability Education in the Digital Age: Effects on Learner Engagement and Environmental Awareness to Support Sustainable Development Goals (SDGs) - Jajang Bayu Kelana; Duhita Savira Wardani; Trisna Nugraha; Galih Septiyan Rahayu (Bumi Publikasi Nusantara, 2025)
This study explores the role of personalized sustainability education (PSE) in promoting learner engagement (LE) and environmental awareness (EA) among elementary school students in Indonesia. Using a quantitative cross-sectional design, data were collected from 114 fifth-grade students across four provinces through validated instruments. Structural Equation Modeling (PLS-SEM) was applied to examine the hypothesized relationships. The results show that PSE has a significant positive effect on both LE and EA, while LE also positively influences EA. Furthermore, PSE mediates the relationship between LE and EA, suggesting that personalization strengthens the translation of engagement into awareness. By making learning experiences more meaningful and contextually relevant, PSE enhances students’ understanding and commitment to sustainability practices. Theoretically, this study advances research on personalized learning and Education for Sustainable Development (ESD). Practically, it highlights the potential of digital personalization strategies to increase engagement, foster awareness, and cultivate pro-environmental behaviors from an early age.